Pemeriksaan Refraksi Subjektif Penderita Presbyopia Status Refraksi Hypermetropia di Optik Boy Semarang - Ithaf Husny Albarrak Khomarudin; Setya Ferywidyastuti; Raden Risang Haryo Chandra Dewantoro (STIKES HAKLI Semarang, 2024)
Hypermetropia, or farsightedness, is a condition where an individual struggles to see nearby objects clearly due to the eyeball's main axis being too short, causing light entering the eye to focus behind the retina. As a result, objects positioned close to the eye cannot be seen clearly by the affected person. The aim of this research is to understand the subjective refraction examination method to determine the lens prescription for both distance and near vision in individuals with presbyopia and hypermetropia refractive status. This study is a descriptive case study that describes the subjective refraction examination cases in presbyopic individuals with hypermetropia refractive status. The research sample was taken from Optik Boy Semarang during the period from October 1 to October 31, 2023, and included individuals with presbyopia and hypermetropia. The findings revealed that among the 58 total patients, 22 individuals (37.93%) had presbyopia with hypermetropia refractive status. Following the refractive examination of two patients (case studies), the prescribed eyeglass prescription was determined to be ODS. S+1.00 D 6/6 with Add S+2.00 and OD S+1.00 OS Plano 6/6 with Add S+3.00. The research concludes that prescribing eyeglasses for presbyopic individuals with hypermetropia refractive status involves correcting near vision by providing addition lenses. For distance vision correction, positive spherical lenses (S+) are prescribed based on the refractive examination results. The emphasis is on the patient's visual comfort without compromising the best monocular vision, assisting in clear vision for both distance and near activities.